PENYULUHAN PENTINGNYA PEMBERIAN MENU SEIMBANG DALAM PENCEGAHAN STUNTING DI KOTA PADANG PANJANG - Dian Puspita; Yusti Siana; Melya Susanti; Rinita Amelia; Mhd Nurhuda (Nusantara Hasana Journal, 2022)
Stunting is a condition in which a child experiences growth disorders, due to that the child's height does not match his age, as a result of chronic nutritional problems, namely, lack of nutritional intake for a long time. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2020 concerning anthropometric standards for assessing the nutritional status of children, stunting or stunting is a nutritional status based on the height-for-age index (TB/U) with a z score of less than -2 SD (standard deviation). Stunting is not only a problem of disrupting physical growth, but also causes children to get sick easily, besides that there are also disturbances in brain and intelligence development, so that stunting is a major threat to the quality of human resources in Indonesia. Indonesia is a country with multiple nutritional problems, marked by a high prevalence of stunting. Based on JME stunting data, UNICEF World Bank in 2020, Indonesia's prevalence of stunting is in 115th position out of 151 countries in the world (Ministry of Health 2020). Basic Health Research Riskesdas  data for 2018 shows the prevalence of stunting in Indonesia is 30.8%. Whereas in 2022 the prevalence of stunted is 24.4 in Indonesia, 23.3% in West Sumatra, and 20% in Indonesia (Ministry of Health 2022). The city government of Padang Panjang through the Health Service (Dinkes) in the strategic plan (Renstra) is trying to reduce the stunting rate to 15.5% in 2023 and 14% in 2024. This reduction is also an effort to support the National Action Plan to Accelerate Reducing Stunting Rates in Indonesia (RAN PASTI) launched by the government through the National Population and Family Planning Agency (BKKBN).